PENYELESAIAN SENGKETA SECARA NEGOSIASI ANTARA PENJUAL DAN PEMBELI DALAM JUAL BELI ONLINE DI ASRINA STORE - Dwikornida , Tessa Sundari Siswati Rahman (Fakultas Hukum Universitas Tamansiswa Padang, 2020)
The implementation of the use of telecommunications technology in national trade can be seen that the use of the internet to support trade transactions no longer requires direct meetings between business actors. These sites require users to become members first, but some are not. As an online store that offers goods to be bought and sold via the internet (E-commerce). Article 1 point 6 of Law No.11 of 2008 concerning Electronic Information and Transactions (UUITE), states: The implementation of an electronic system is the use of electronic systems by state administrators, individuals, business entities and / or the community. between the seller and the buyer will be higher, in most cases disputes between the buyer and the seller where communication cannot solve the problem. Based on the results of the research, it is obtained data that the settlement of disputes between sellers and buyers at the Asrina Store is carried out by negotiating via the internet between the two parties. The buyer will contact the seller for items that are not in accordance with the order and after that the seller will ask the buyer to send the item back to the seller to be exchanged for a new one. The obstacles they face are that this negotiation cannot be carried out directly or face to face due to distance and circumstances that are not possible, consumers who do not want to pay shipping costs to sellers and consumers who do not immediately report if there are items that do not match their orders. The solution is for consumers who do not want to pay postage, the seller will bear all the costs until the goods arrive at the buyer.